2011
DOI: 10.1074/jbc.m110.175810
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Optineurin in Neuronal Cells

Abstract: Optineurin is a gene linked to amyotrophic lateral sclerosis, Paget disease of bone, and glaucoma, a major blinding disease. Mutations such as E50K were identified in glaucoma patients. We investigated herein the involvement of ubiquitin-proteasome pathway (UPP) and autophagy, two major routes for protein clearance, in processing of optineurin in a retinal ganglion cell model line RGC5 and neuronal PC12 cells. It was found that the endogenous optineurin level in neuronal cells was increased by treatment of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 67 publications
7
83
0
Order By: Relevance
“…OPTN itself is typically degraded by the proteasome, and is a known autophagy cargo adaptor (Shen et al, 2011). Thus, our data showing LC3 colocalization strongly suggest puncta stem from autophagic vesicles, instead of aberrant OPTN degradation (Shen et al, 2011). Overall, our findings are consistent with the observations that autophagy is impaired in PD brains and models, where alpha-synuclein accumulation has been intensely investigated (Mader et al, 2012;Tan et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…OPTN itself is typically degraded by the proteasome, and is a known autophagy cargo adaptor (Shen et al, 2011). Thus, our data showing LC3 colocalization strongly suggest puncta stem from autophagic vesicles, instead of aberrant OPTN degradation (Shen et al, 2011). Overall, our findings are consistent with the observations that autophagy is impaired in PD brains and models, where alpha-synuclein accumulation has been intensely investigated (Mader et al, 2012;Tan et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…Both autophagic dysfunction and neuroinflammation occur in PD and are linked to pathogenesis (Macchi et al, 2015;Tan et al, 2014). OPTN itself is typically degraded by the proteasome, and is a known autophagy cargo adaptor (Shen et al, 2011). Thus, our data showing LC3 colocalization strongly suggest puncta stem from autophagic vesicles, instead of aberrant OPTN degradation (Shen et al, 2011).…”
Section: Discussionmentioning
confidence: 55%
“…4B). 54,55 Thus, Wild et al identified a putative LC3-interacting region (LIR) located in the N-terminal domain of Optn (Fig. 2B).…”
mentioning
confidence: 99%
“…Furthermore, OPTN has been recently identified as an autophagy receptor involved in the clearance of cytosolic Salmonella (Wild et al, 2011). The mechanisms by which OPTN causes the optic pathology are still unclear; however, it has been shown that overexpression of wild-type optineurin or its Glu50Lys (E50K) mutant in RGC-5 cultures activates autophagy and treatment with rapamycin reduced the level of apoptosis elicited in these conditions (Shen et al, 2011). Those data were also validated by in vivo finding showing an induction of autophagy in the retina of transgenic mice carrying the optineurin E50K mutation (Shen et al, 2011).…”
Section: Genetic Models Of Glaucomamentioning
confidence: 99%